Development of Digital Assessment of Science Process Skills on Occupational Safety and Health Topics in Chemical Laboratories - Muhammad Bayu Kusuma; Nahadi Nahadi (Eduvest - Journal of Universal Studies, 2025)
This research aims to develop a digital-based science process skill assessment (PPP) focused on the topic of occupational safety and health (K3) in chemistry laboratories. Development was carried out using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects consisted of students of the Chemistry Education Study Program at one of the universities in Indonesia. Data was obtained through surveys and analysis of student responses regarding knowledge and attitudes towards K3 practice. The assessment instrument is developed based on PPP indicators and validated by experts. The results of initial observations show that most students understand the importance of K3, but there are still gaps in the practical application of the concept of K3. The development of this digital assessment is expected to increase students' readiness to face laboratory practicum in a safe and structured manner.